6-Gingerol inhibits hair cycle via induction of MMP2 and MMP9 expression - HOU,CHUN (2017)
ABSTRACT 6-Gingerol is the major active constituent of ginger. In the current study, we aimed to investigate the mechanisms underlying the effects of 6-Gingerol on hair growth. Mice were randomly divided into five groups; after hair depilation (day 0), mice were treated with saline, or different concentrations of 6-Gingerol for 11 days. The histomorphological characteristics of the growing hair follicles were examined after hematoxylin and eosin staining. The results indicated that 6-Gingerol significantly suppressed hair growth compared with that in the control group. And choose the concentration of 6-Gingerol at 1 mg/mL to treated with mice. Moreover, 6-Gingerol (1 mg/mL) significantly reduced hair re-growth ratio, hair follicle number, and hair follicle length, which were associated with increased expression of MMP2 and MMP9. Furthermore, the growth factors, such as EGF, KGF, VEGF, IGF-1 and TGF-β participate in the hair follicle cycle regulation and regulate hair growth. We then measured the concentrations of them using ELISA assays, and the results showed that 6-Gingerol decreased EGF, KGF, VEGF, and IGF-1 concentrations, and increased TGF-β concentration. Thus, this study showed that 6-Gingerol might act as a hair growth suppressive drug via induction of MMP2 and MMP9 expression, which could interfere with the hair cycle.